Immunogenicity of a foot-and-mouth disease (FMD) vaccine against serotypes O, A, SAT-2, and Asia-1 in the Middle East and many parts of Africa, Southeast Asia and Europe - Momtaz Wasfy; Abdel Hamid Bazid; Mohamed Nayel; Emad B. Ata; Wael K. Elfeil; Mohamed Attia; Magdy Elsayed (Virology Journal)
Abstract Control of foot-and-mouth disease (FMD) is hampered by inadequate biosecurity measures, border transcending serotype strains and unavailability of broad coverage vaccines. In this investigation, six FMD antibody-free calves, aged 1.5–2 years, received a tetravalent, inactivated, aluminum hydroxide gel vaccine (Aphthovac-4) containing 6 PD50/dose of certain strains for protection against a wide range of strains in the Middle East, Africa, Southeast Asia, and parts of Europe. The vaccine contained 2 strains of serotype A/Asia (A/Asia (A/Iran-05 and A/Ind/40/2000 G-VII), 2 of serotype O (O/Middle East-South Asia topotype and O/Manisa/TUR/69), and one strain each of serotype SAT-2 (topotype VII) and Asia-1 (Sindh-8). Primary and booster doses were administered 3 weeks apart and sera were collected one week after the booster vaccination, preserved frozen then shipped to The Pirbright Institute, UK, for antibody evaluation by virus neutralization test (VNT) against 22 lineages circulating in the targeted regions. Serum titers against test strains of serotype A were high (range = 355– < 1413 or 2.6– < 3.15 log10), and those demonstrating relatively lower values included A/Irn/25/18 (G-VII), A/Irn-05 Far-11, A/Iran05 SIS-13 and SEA-97. Serotype O test strains presented higher titers (≤ 1/1413 or ≤ 3.0 log10), but O/Cathay, O/Panasia-2 ant-10 and one O/Ind-2001e lineage exhibited somewhat lower values (range (355–1024 or 2.6–3.01 log10). Antibodies against SAT-2 test strains (XIV Topotype) ranged between 128 and 178 (1.9–2.2 log10) in 5 animals (5/6, 83%), despite the reported high r1 values. Likewise, Asia-1 strain elicited a similar titer range against IRN/1/2020 in the same 5 animals. The 6th animal generally showed one dilution less. The results portray a dynamic antigenic change between the vaccinal and test strains, underscoring the value of strain matching, use of high payload and incorporation of double antigen lineages within each serotype to broaden coverage in enzootic and epizootic situations.